HUBUNGAN GROWTH MINDSET DENGAN PENGAMBILAN KEPUTUSAN KARIR PADA PESERTA DIDIK KELAS XI SMA NEGERI 2 RANAH BATAHAN - Elisa Nadiroha; Yasrial Chandra; Suryadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by students who appear afraid to answer teachers' questions in class, are less receptive to criticism, are hesitant in planning further education or work after graduation, blame themselves for learning difficulties, choose majors that do not match their talents and interests, are influenced by peers in determining their major, and lack confidence and feel pessimistic when considering further education. This study aims to describe: 1) the growth mindset of eleventh-grade students at SMA Negeri 2 Ranah Batahan; 2) their career decision-making; and 3) the relationship between growth mindset and career decision-making among these students. This study employed a quantitative descriptive method with correlational analysis. The sample of 86 students was determined using proportional random sampling. The instrument used was a questionnaire, consisting of 27 items for the growth mindset variable and 28 items for the career decision-making variable. Data analysis included descriptive analysis, prerequisite tests, and the Pearson Product Moment correlation test. The results show that: 1) students' growth mindset is in the high category; 2) students' career decision-making is in the high category; 3) there is a significant relationship between growth mindset and career decision-making with a moderate coefficient. It is therefore recommended that guidance and counseling teachers as well as subject teachers provide services and materials that can help raise students' growth mindset from the high to the very high category so that their career decision-making ability can develop optimally.